Co-creation in effectuation processes: A stakeholder perspective on commitment reasoning - Mumford Jonathan Van; Zettinig Peter (Elsevier, 2022)
In this article, we seek to contribute to theory on market co-creation through effectuation. To achieve this goal, we examine the different kinds of reasoning behind stakeholder commitments in effectuation processes. Although effectual and causal logics sufficiently account for decision-making in instrumental rationality, scholars have paid little attention to value rationality, and how it might influence stakeholder commitments and behavior. Different commitments may follow different rationales, ranging from instrumentally rational commitments based on causal or effectual logics, to value rational commitments based on state-belief or change-belief. The typology of these four commitment reasoning types provides a framework for analyzing stakeholder behavior based on different perceptions of the commitment decision space. Our typology shows that commitments based on value rationality may be qualitatively different from those driven by instrumental rationality and that value rationality may enable commitments under conditions that preclude instrumentally rational actions. Furthermore, different commitments influence market co-creation processes in different ways. In this article, we examine how different commitments affect (1) conflict and effectual churn and (2) the relative path dependence, or shapability, of the market co-creation space. Based on this typology, we propose avenues for future research on co-creation in effectuation processes, with a special focus on stakeholders.